Seroprevalence of dengue, Zika, chikungunya and Ross River viruses across the Solomon Islands. - Tanya L Russell; Paul F Horwood; Humpress Harrington; Allan Apairamo; Nathan J Kama; Albino Bobogare; David MacLaren; Thomas R Burkot (Public Library of Science (PLoS), 2022)
Across the Pacific, and including in the Solomon Islands, outbreaks of arboviruses such as dengue, chikungunya, and Zika are increasing in frequency, scale and impact. Outbreaks of mosquito-borne disease have the potential to overwhelm the health systems of small island nations. This study mapped the seroprevalence of dengue, Zika, chikungunya and Ross River viruses in 5 study sites in the Solomon Islands. Serum samples from 1,021 participants were analysed by ELISA. Overall, 56% of participants were flavivirus-seropositive for dengue (28%), Zika (1%) or both flaviviruses (27%); and 53% of participants were alphavirus-seropositive for chikungunya (3%), Ross River virus (31%) or both alphaviruses (18%). Seroprevalence for both flaviviruses and alphaviruses varied by village and age of the participant. The most prevalent arboviruses in the Solomon Islands were dengue and Ross River virus. The high seroprevalence of dengue suggests that herd immunity may be a driver of dengue outbreak dynamics in the Solomon Islands. Despite being undetected prior to this survey, serology results suggest that Ross River virus transmission is endemic. There is a real need to increase the diagnostic capacities for each of the arboviruses to support effective case management and to provide timely information to inform vector control efforts and other outbreak mitigation interventions.